Whole-Genome Sequencing for Molecular Characterization of Carbapenem-Resistant Enterobacteriaceae Causing Lower Urinary Tract Infection among Pediatric Patients - Hassan Al Mana; Sathyavathi Sundararaju; Clement K. M. Tsui; Andres Perez-Lopez; Hadi Yassine; Asmaa Al Thani; Khalid Al-Ansari; Nahla O. Eltai (MDPI AG, 2021)
Antibiotic resistance is a growing public health problem globally, incurring health and cost burdens. The occurrence of antibiotic-resistant bacterial infections has increased significantly over the years. Gram-negative bacteria display the broadest resistance range, with bacterial species expressing extended-spectrum β-lactamases (ESBLs), AmpC, and carbapenemases. All carbapenem-resistant Enterobacteriaceae (CRE) isolates from pediatric urinary tract infections (UTIs) between October 2015 and November 2019 (n = 30). All isolates underwent antimicrobial resistance phenotypic testing using the Phoenix NMIC/ID-5 panel, and carbapenemase production was confirmed using the NG-Test CARBA 5 assay. Whole-genome sequencing was performed on the CREs. The sequence type was identified using the Achtman multi-locus sequence typing scheme, and antimicrobial resistance markers were identified using ResFinder and the CARD database. The most common pathogens causing CRE UTIs were E. coli (63.3%) and K. pneumoniae (30%). The most common carbapenemases produced were OXA-48-like enzymes (46.6%) and NDM enzymes (40%). Additionally, one E. coli harbored IMP-26, and two K. pneumoniae possessed mutations in ompK37 and/or ompK36. Lastly, one E. coli had a mutation in the marA porin and efflux pump regulator. The findings highlight the difference in CRE epidemiology in the pediatric population compared to Qatar's adult population, where NDM carbapenemases are more common.